Orbital altitude dust at Mars, its implication and a prototype for its detection. (15th October 2018) - Pabari, J.P.; Haider, S.A.; Pandya, B.M.; Singh, R.K.; Kumar, A.; Patel, D.K.; Bogavelly, A.
Abstract: Dust at orbital altitude on Mars could be mainly due to interplanetary source, cometary source or natural satellites of Mars. Recent work and MAVEN observations predict that dust at orbital altitudes could be interplanetary in nature. Since, the source of such particles is not understood unambiguously, it remains a puzzling question to space scientist about what is a source of it. An instrument on future Mars orbiter, which can measure the dust particle parameters like mass, velocity and flux, may be helpful to address such issues. In this article, dust flux at orbital altitudes on Mars is presented in the initial part. To study origin, abundance, distribution, flux and seasonal variation of dust at orbital altitude on Mars, a Mars Orbit Dust Experiment (MODEX) has been proposed and development of its prototype has been initiated at Physical Research Laboratory. Though, earlier dust detectors by other researchers might have been designed using the impact plasma theory, they are not found with thorough explanation explicitly, in the literature. We have presented the impact plasma theory for the first time to explain detector target design. Also, a prototype dust detector, its front end electronics and initial testing results using a pulse laser are reported here. The ions and electrons of impact plasma have been separated using biased electrodes. The results demonstrate the possible use of pulse laser for testing the impact ionization dust detector, prior to calibrating the dust detector using a dust accelerator facility. The detector under development could provide actual dust flux coming to Mars and using the measurements, one can understand the origin, abundance, distribution, flux and seasonal variation of dust. Highlights: Most likely source of orbital altitude dust at Mars is interplanetary. Dust flux at Mars is derived based on the most practical model for micrometeorites and results agree with that given by MAVEN. Dust density is given for the incoming micrometeorites at Mars and typically it is 10 −7 #/m 3 . Impact theory is presented for the detector target design. A prototype dust detector design and testing are carried out.